HOUSEHOLD FOOD DEMAND IN INDONESIA: A TWO-STAGE BUDGETING APPROACH - Agus Widarjono; Sarastri Mumpuni Rucbha (Faculty of Economics and Business, Universitas Gadjah Mada, 2016)
A two-stage budgeting approach was applied to analyze the food demand in urban areas separated by geographical areas and classified by income groups. The demographically augmented Quadratic Almost Ideal Demand System (QUAIDS) was employed to estimate the demand elasticity. Data from the National Social and Economic Survey of Households (SUSENAS) in 2011 were used. The demand system is a censored model because the data contains zero expenditures and is estimated by employing the consistent two-step estimation procedure to solve biased estimation. The results show that price and income elasticities become less elastic from poor households to rich households. Demand by urban households in Java is more responsive to price but less responsive to income than urban households outside of Java. Simulation policies indicate that an increase in food prices would have more adverse impacts than a decrease in income levels. Poor families would suffer more than rich families from rising food prices and/or decreasing incomes. More importantly, urban households on Java are more vulnerable to an economic crisis, and would respond by reducing their food consumption. Economic policies to stabilize food prices are better than income policies, such as the cash transfer, to maintain the well-being of the population in Indonesia Keywords: Urban, Two-Stage Budgeting, QUAIDS, Price and Income elasticity